The Related Qualitative Study About Diabetes In The Eastern Region Of Indonesia: The Understanding, The Health Belief, And The Behaviors Of Diabetes Type 2 Patients - Sulistiyani; Ninef, Violin Irene; Rahayu, Endah Sri; Payasan, Lalu Guntur; Parera, Magdalena Junu (Journal of Social And Education Research, 2025)
Diabetes has steadily increased in the last two decades. Studies show people's behavior in managing diabetes is very complex and influenced by cultural beliefs and values. This research describes the understanding, belief, and related behaviors toward the diabetes mellitus of Diabetes Mellitus type II patients in the Eastern region of Indonesia. The researchers grouped the participants in a semi-structured focus group. The group consisted of 12 participants aged between 45 and 55 years old. The focused group was useful to obtain the perspective, experience, and attitude about diabetes. The researchers analyzed the qualitative data with the Health Belief Model as the analytical framework to identify the patterns and the main findings. The analysis results found five primary themes related to understanding, belief, and diabetic behavior. The themes were: The diabetic understanding of the Eastern regional communities such as the cultural problem and the role of local beliefs to treatment diabetes. The tradition and the modern medical approach, the challenges of healthy lifestyle practice, the psychological impacts of diabetes on health, and the expectations and the challenges of the local health system.The researchers expect the findings could be the principle for developing more directed and effective interventions